Intuitionistic Fuzzy Magnified Translation of PS-Algebra - Rakib Iqbal; Zafar Iqbal; Mohsin Khalid (Journal of New Theory)
In this paper, the concepts of intuitionistic fuzzy α-translation (IFAT), intuitionistic fuzzy α-multiplication (IFAM), and intuitionistic fuzzy magnified βα-translation (IFMBAT) are introduced in the setup of PS-algebra. Some properties of PS-ideal and PS-subalgebra are investigated by applying the concepts of IFAT, IFAM, and IFMBAT. Intersection and union of intuitionistic fuzzy PS-ideals are explained through results and examples.